Praise and its Relation to Other Phenomena (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the phenomenon of praise, its role in various social, psychological and cultural contexts and its relationship with other relationships. Praise plays an important role in human relations, in particular, in the formation of social interactions, motivation, and psychological states. The article also examines the importance of praise in various fields, including teaching, workplace leadership, cultural and artistic fields, and how it affects social and cultural attitudes